EFFICACY OF PHYSICAL EXERCISES IN PATIENTS WITH OSTEOPOROTIC VERTEBRAL FRACTURES - Lyudmila P Evstigneeva; E V Kozhemyakina; E V Negodaeva; G A Gusel'nikova; A A Belkin; D N Vikulova; N V Belkin; O M Lesnyak (Научно-практическая ревматология, 2014)
Vertebral fractures in osteoporosis (OP) patients are accompanied by a decrease in quality of life (QoL) and functional limitations. Physical activity is often recommended for such patients to reduce pain, improve QoL, and functional status.Objective. To assess the impact of exercises on QOL, functional performance, and balance in patients with osteoporotic vertebral fractures.Material and Methods. The study included 78 women with vertebral fractures and chronic back pain (40 patients in the study group and 38 patients in the control group). The average age of patients in the study group was 70.7 ± 8.1 years; in the control – 67.6 ± 7.0 years (p = 0.35). The studied parameters did not significantly differ for two groups at the beginning of the study. In the study group, physical exercises were conducted for 40 minutes twice a week during 12 months. Patients in the control group were recommended to follow the same physical activity as it was prior to the study. Evaluation of the studied parameters at study baseline and 12 months later was carried out using the QUALEFFO-41 questionnaire, a computer system for disequilibrium diagnostics and the «Stand up and walk» test.Results. After 12 months, a statistically significant improvement in QoL was observed among patients of the study group, both in the total score (41.2) compared with the control (57.3, p<0.0001), and in values of all domains, as well as results of the «Rise from a sitting position» and «Chasse step» balance tests. After 12 months, the study group showed a statistically significant reduction of time required to execute the «Stand up and walk» test from 12.1 ± 3.8 to 10.8 ± 2.5 s (p = 0.028), while no changes were observed in the control group (11.1 ± 3.4 and 11.1 ± 2.8 s respectively). Exercises improve QoL, functional activity and balance in patients with osteoporotic vertebral fractures.